PERAN PAGUYUBAN MASYARAKAT IKAN (PAMIK) DALAM MENINGKATKAN PENDAPATAN ANGGOTA DI DUSUN REKESAN KECAMATAN JAMBUWER KABUPATEN MALANG TAHUN 2014 - Nina Wiranti; Pudjo Suharso (Economic Education, University of Jember, 2015)
Paguyuban informal an organization formed based on some of the causes together for our common endeavour. PAMIK is one of the traditional organization formed the surrounding community hamlet Rekesan Kabupaten Malang based on a shared interest to the purpose are predetermined in advance. This research aims to understand the role of paguyuban the community fish (PAMIK) in improving the income members in hamlet Rekesan Kecamatan Jambuwer Kabupaten Malang in year 2014. The determination of recipient the research uses a method of purposive area, while the determination of informants the research uses a method of sampling which is purposive infoman basic research is the chairman and the treasurer PAMIK and informants additional is a member of PAMIK. Data collection using methods interview, documentation and observation. An analysis of the data used in this research was the reduction of the data, display data, and the withdrawal of conclusion. The result showed that the PAMIK in increasing income divides into two is in economic and a social. PAMIK role in the economy, to increase member 's income includes raising revenues and providing jobs. As for the role of the social PAMIK are the socialization or training in cultivating fish and builds solidarity between PAMIK by the public.